Productive performance of post-weaning piglets supplemented with essential oil of wild garlic (Mansoa alliacea L.).Technical note - Caicedo, W.; Caicedo, L.; Buenaño, C.; Caicedo, María (Cuban Journal of Agricultural Science, 2023)
The use of essential oils constitutes an alternative to reduce or eliminate the dependence on antibiotics and synthetic growth promoters and also decrease the microbial resistance and residuality on pig’s carcass. With the purpose of evaluating the effect of essential oil of wild garlic (Mansoa alliacea L.) on the productive performance of post-weaning piglets, a total of 24 castrated male piglets, commercial cross (Blanco Belga x Duroc x Pietrain) of 28 days of age, with average live weight of 9.33 ± 0.34 kg were used. The animals were distributed according to a complete random design and each one constituted an experimental unit. The treatments consisted in a control diet (0); 500 mg of essential oil of wild garlic.kg DM-1 and 1000 mg of essential oil of wild garlic.kg DM-1, respectively. The variables food intake day (FID), weight gain per day (WGD), feed conversion (FC) and final weight (FW) were studied. There was not significant effect (p > 0.05) between treatments for the variables under study. It is concluded that under this research conditions is viable the use of essential oil of wild garlic as natural additive in post-weaning piglets diets, with the purpose of reducing the dependence on antibiotics and synthetic growth promoters of the food which are commercialize in Ecuador for this category. Key words: essential oil, phytobiotic additive, productive indexes, commercial piglets